Book Reviews (The Muslim world, 1972)
Book Review in this articles The Cambridge History of Islam The Fihrist of al. Nadim, A Tenth-Century Survey of Muslim Culture Kitǎb al-Tawhid. The Islamic Law of Nations, Shaybian' Siyar The Unholy War: Israel and Palestine Bibliographie Der Afghanistan-Literatur